Understanding Consumer Loyalty to Revlon: An Empirical Study of Product Quality and Brand Image - Salmadiva, Jacynda; Rofiaty (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The objective of this research is to identify the effects of product quality and brand imageonthe loyalty of Revlon consumers in Mojokerto City. This quantitative explanatory studywasconducted to develop and validate the causal relationships between its variables through hypothesis testing. From the population of Revlon consumers residing in Mojokerto City, 110people were selected as the respondents through non-probability sampling methodandpurposive sampling technique. The research instruments have been tested for reliabilityandvalidity, and the acquired data was processed through multiple linear regression after passingthe classical assumption tests. All of the statistical processes were performed inIBMStatistics 25. This study finds that product quality positively and significantly influences the consumer loyalty and that brand image also positively and significantly affects the consumer loyalty. Based on the findings, it can be concluded that product quality and brandimagesimultaneously influence the loyalty of Revlon consumers in Mojokerto City.